Mepolizumab improves small airway function in severe eosinophilic asthma. (March 2019) - Farah, Claude S.; Badal, Tanya; Reed, Nicola; Rogers, Peter G.; King, Gregory G.; Thamrin, Cindy; Peters, Matthew J.; Seccombe, Leigh M.
Abstract: Background and objective: Treatment with mepolizumab in severe eosinophilic asthma (SEA) significantly reduces exacerbations with modest improvements in symptom control and spirometry. The time course of any changes in small airway function is unknown. Objective: To describe changes in ventilation inhomogeneity, a marker of small airway function, after commencing mepolizumab. Methods: Prospective cohort of 20 adults (12 male) with SEA commencing monthly mepolizumab. Measurements at baseline, Week 4 and Week 26 included the Asthma Control Questionnaire (ACQ-5), spirometry, fraction of exhaled nitric oxide (FeNO) and multiple breath nitrogen washout to measure global (Lung Clearance Index, [LCI]) and regional ventilation inhomogeneity in acinar (Sacin) and conducting (Scond) airways. Other asthma therapy remained unchanged between baseline and Week 4. Treatment related changes were assessed using RM-ANOVA and paired t-tests. Relationships between changes in lung function and symptoms were assessed by Pearson's correlation. Results: At Week 4, ACQ-5, spirometry, LCI and Sacin improved significantly (p < 0.04) and all were sustained at Week 26. The change in ACQ-5 correlated with the change in Sacin (r = 0.48, p = 0.03) and FRC (r = 0.46, p = 0.04), but not spirometry. Conclusion: Improved symptom control improved rapidly after commencing mepolizumab in patients with SEA. The early improvement in small airway function was associated with asthma control and may be a significant contributor to the therapeutic response. Highlights: Abnormal small airway function is important in severe eosinophilic asthma. Mepolizumab improves small airway function after the first subcutaneous injection. The change in acinar airway function following the commencement of mepolizumab relates to the improved symptom control. Therapies that target small airway function can improve patient outcomes.